2007
DOI: 10.1016/j.jmb.2007.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Apparent Free Energy of Helix–Helix Dimerization in a Biological Membrane Due to Point Mutations

Abstract: SummaryWe present an implementation of the TOXCAT membrane protein self-association assay that measures the change in apparent free energy of transmembrane helix dimerization caused by point mutations. Quantifying the reporter gene expression from cells carrying wild type and mutant constructs shows that single point mutations that disrupt dimerization of the transmembrane domain of glycophorin A reproducibly lower the TOXCAT signal more than one hundred-fold. Replicate cultures can show up to three-fold chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 55 publications
7
82
1
Order By: Relevance
“…These results indicate that the amino acid at position 45 plays crucial roles in both folding and the Vpu susceptibility of the hu-tetherin TM domain. This is consistent with biochemical characteristics of threonine; in general, threonine is rare in TMs of proteins; however, if it exists, the threonine can play very important roles in the folding and protein-protein interaction of TMs (49), such as the tight packing of helices (14), the formation of intermolecular hydrogen bonds (13,62), and the formation of biologically functional protein complexes (3). Therefore, it is conceivable that T45 in hu-tetherin plays key roles in forming a biologically functional complex of hu-tetherin, Vpu, and undefined proteins for the Vpu-mediated degradation of tetherin.…”
Section: Discussionsupporting
confidence: 61%
“…These results indicate that the amino acid at position 45 plays crucial roles in both folding and the Vpu susceptibility of the hu-tetherin TM domain. This is consistent with biochemical characteristics of threonine; in general, threonine is rare in TMs of proteins; however, if it exists, the threonine can play very important roles in the folding and protein-protein interaction of TMs (49), such as the tight packing of helices (14), the formation of intermolecular hydrogen bonds (13,62), and the formation of biologically functional protein complexes (3). Therefore, it is conceivable that T45 in hu-tetherin plays key roles in forming a biologically functional complex of hu-tetherin, Vpu, and undefined proteins for the Vpu-mediated degradation of tetherin.…”
Section: Discussionsupporting
confidence: 61%
“…The strong sequence conservation across syndecan ortholog TMDs thus probably reflects the conservation of paralog-specific TMD interaction propensities. We expect that the close correspondence between measures of syndecan TMD dimerization from membranes and detergents, which has also been seen for GpA (47), will facilitate biochemical and structural investigations of syndecan TMD complex formation.…”
Section: Discussionmentioning
confidence: 66%
“…The CAT activities were further corrected for construct expression as mutations can modulate the TOXCAT signal. 19 Therefore, the effects of individual mutations on CAT levels provided insights into the physical basis for dimerization. Our TOXCAT results showed that mutation of each Leu residue to Ala decreased CAT activity to some extent [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the TOXCAT signals can arise from differences in the self-association of the membrane-inserted fusion proteins but may also reflect variations in the total amounts of fusion protein expressed. 19 In our experimental data, the CAT activities were corrected for construct expression and only reflect the self-association of the membrane-inserted fusion proteins. We found that mutating most of the residues to Ala decreased the CAT activity, whereas mutating each nonpolar residue to Leu increased the CAT activity, which suggested that the Ibb TM domain is dimerized via a leucine zipper-like heptad repeat pattern of amino acids.…”
Section: Discussionmentioning
confidence: 99%